Narrative Review: Optimation of Ethanol as a Solvent for Flavonoid Compounds in Papaya Leaf Extraction - Davit Nugraha; Anna L Yusuf; Panji Wahlanto (Ad-Dawaa : Journal of Pharmacy, 2023)
Ethanol is widely used as a distiller of secondary metabolite compounds. Ethanol very well dissolves secondary metabolite compounds including flavonoids group compounds including for papaya (Carica papaya L.) leaf extraction. This review was conducted to examine solvent optimization that has been used in various original studies. The method of searching scientific journal article using PubMed and MDPI using keyword “extraction and ethanol and flavonoid and carica papaya leaf” with the inclusion criteria of 2018 – 2023 article, free full text and not review articles, the number of article obtained was 3 articles. The optimal concentration of ethanol as a flavonoid extract solven is 70 % ethanol at temperatures from 30 °C – 50°C with a time range of 10 – 48 hours of immersion.